Sulfoethylated nanofibrillated cellulose: Production and properties. (1st August 2017) - Naderi, Ali; Koschella, Andreas; Heinze, Thomas; Shih, Kuo-Chih; Nieh, Mu-Ping; Pfeifer, Annett; Chang, Chung-Chueh; Erlandsson, Johan
Highlights: Sulfoethylated nanofibrillated cellulose was produced by an attractive method. The nanofibrillated cellulose displayed interesting redispersion properties. The nanofibrillated cellulose displayed high stability in varying pH-conditions. Abstract: Sulfoethylated nanofibrillated cellulose (NFCSulf ) was produced by an industrially relevant process. The properties of the NFCSulf were compared with those of carboxymethylated nanofibrillated cellulose (NFCCarb ), which has been identified as an attractive NFC for several industrial applications. The investigations revealed that NFCSulf is characterized by a higher degree of fibrillation and has superior redispersion properties. Furthermore, NFCSulf displays higher stability in varying pH values as compared to NFCCarb . Hence, NFCSulf may be a more attractive alternative than NFCCarb in applications such as rheological modifiers or adsorbing components in personal care products, in which the performance of NFC must remain unaffected in varying ambient conditions. The superior properties of NFCSulf compared to NFCCarb were proposed to be due to the combination of the unique chemical characteristics of the sulfoethylated reagent, and the larger size of the sulfonate group compared to the carboxymethyl group.